How do chief digital officers pursue digital transformation activities? The role of organization design parameters - Singh, Anna; Klarner, Patricia; Hess, Thomas (Long range planning, 2020)
While an increasing number of companies are establishing Chief Digital Officer (CDO) positions to support their digital transformation (DT), there has been very little research on how CDOs can pursue DT activities in their organizations. We conducted a multiple-case study to investigate the organization design parameters surrounding CDOs and their DT activities. Our study contributes to research on strategic change by showing how, once CDOs have been appointed, they need to be embedded in the organization by (vertically) anchoring them in the organization's structure, depending on the firm's DT strategy and the CDO's task focus. Further, CDOs combine different formal and informal activities to coordinate (horizontally) between employees working on DT activities in different units and at different hierarchical levels. We also contribute to organization design research by providing insights into how a firm's DT strategy, its CDO's hierarchical position, and the CDO's task focus have to be aligned in order to digitally transform a company.